Wort - Satz - Korpus: Multimethodische digitale Forschung in der Linguistik - Posch, Claudia; Irschara, Karoline; Rampl, Gerhard (innsbruck university press, 2022)
Corpora, corpus linguistic methods and instruments of corpus creation have experienced an unprecedented upswing within linguistics in recent years. The present volume poses the question to what extent we can now speak of digital linguistics. The contributions in this volume address different data-driven as well as corpus-based procedures, as well as the creation and composition of linguistic text corpora and reflect the methodological diversity of digital linguistic disciplines.